The social ideal of the domestic school/RN - reports from a memory (Research, Society and Development, 2021)
The present work discusses the foundation of the  Domestic School of Natal/RN and proves the model of the feminine school starting from the study of Childcare. Aiming to analyze the trajectory of the mentioned school, intending to understand the path to its foundation (1914) and the advances that brought contributions in the social, intellectual and technological fields analyzed after its insertion in the Potiguar capital. Our work is supported by its importance as a Domestic School institution for Natal society. For being a reference for institutions of female education in Brazil, as the teachings promoted a differentiated focus on the curriculum, by providing a modern and cultured education to the students. With learning aimed at their health, by providing care and healthy growth of children through the study of childcare. This research is developed within the scope of Cultural History, theoretically-methodologically grounded through documentary and bibliographic sources about the Domestic School of Natal. Supported by the concepts of Memory; Modernization; Childcare; Women's Education; Social, Cultural, Historical and Political Context pointing to the analyzed period. We conclude that the desire to provide a modern education and scientific training with theoretical and practical knowledge necessary for the education of young girls in the State of Rio Grande do Norte, was a milestone for female education.